Respuestas
Respuesta dada por:
2
¡Hola!
Vamos a hacer la propiedad distributiva al eliminar los paréntesis
![6(x+5)-5x=25 6(x+5)-5x=25](https://tex.z-dn.net/?f=6%28x%2B5%29-5x%3D25)
![6x + 30 - 5x = 25 6x + 30 - 5x = 25](https://tex.z-dn.net/?f=6x+%2B+30+-+5x+%3D+25)
![6x - 5x = 25 - 30 6x - 5x = 25 - 30](https://tex.z-dn.net/?f=6x+-+5x+%3D+25+-+30)
![\boxed{\boxed{x = - 5}}\end{array}}\qquad\checkmark \boxed{\boxed{x = - 5}}\end{array}}\qquad\checkmark](https://tex.z-dn.net/?f=%5Cboxed%7B%5Cboxed%7Bx+%3D+-+5%7D%7D%5Cend%7Barray%7D%7D%5Cqquad%5Ccheckmark)
Vamos a hacer la propiedad distributiva al eliminar los paréntesis
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años